2017
DOI: 10.3390/act6020017
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Effects on the Polypyrrole Tri-layer Actuator

Abstract: Abstract:Electroactive polymer actuators such as polypyrrole (PPy) are exciting candidates to drive autonomous devices that require low weight and low power. A simple PPy tri-layer bending type cantilever which operates in the air has been demonstrated previously, but the environmental effect on this actuator is still unknown. The major obstacle in the development of the PPy tri-layer actuator is to create proper packaging that reduces oxidation of the electrolyte and maintains constant displacement. Here, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Generally, PPy films deposited at 1 mA current for 12 h Are found to be uniformly thick on both sides and show the cauliflower-type of structure with different sizes. , The size of features on the surface gets larger for longer deposition times. In our case, with a 12 h long deposition, the polymerization period provides good film adhesion as well as good crystalline structure morphology Figure b demonstrates the sharp X-ray diffraction (XRD) peak of a PPy-deposited film at 2θ = 23.1°, with the relative full width at half maximum at 1.34° and long range XRD with an LiTFSi peak with PPy as demonstrated in the Supporting Information S3 .…”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…Generally, PPy films deposited at 1 mA current for 12 h Are found to be uniformly thick on both sides and show the cauliflower-type of structure with different sizes. , The size of features on the surface gets larger for longer deposition times. In our case, with a 12 h long deposition, the polymerization period provides good film adhesion as well as good crystalline structure morphology Figure b demonstrates the sharp X-ray diffraction (XRD) peak of a PPy-deposited film at 2θ = 23.1°, with the relative full width at half maximum at 1.34° and long range XRD with an LiTFSi peak with PPy as demonstrated in the Supporting Information S3 .…”
Section: Resultsmentioning
confidence: 63%
“…The trilayer PPy actuator is an anion-driven device, and the deflection of the actuator is caused by volume change of the conducting polymer due to the redox reaction. , In a trilayer actuator, layers of PPy are separated by the porous insulating film made of polyvinylidene fluoride (PVDF), which contains an electrolyte inside the pores. When dc electric voltage is applied on a PPy actuator, the volume of the PPy film at the positive electrode expands due to oxidation, whereas the film volume shrinks on the negative side because of reduction .…”
Section: Introductionmentioning
confidence: 99%
“…As a result, CP has limited application in large-scale actuators. [125,126] In trilayer configuration, the energy consumed is used two times to produce the reactions and volume variations. [126] Studies reveal that the CP actuator has many advantages over traditional ionic-polymermetal-composites in terms of conductivity, biocompatibility, responsive ability, and tunable properties.…”
Section: Bioactuatorsmentioning
confidence: 99%
“…A good example of such anion-driven electroactuators is PPy/TFSI. The film can produce significant output stain and stress when subjected to TFSI ‒ -enriched organic solvents such as propylene carbonate (PC), methanol or 2-propanol [48,49], making the electrochemomechanical performance of such electroactuators dependent on the solvent. Hara et al reported that the volumetric strain decreased from 33.1% to 20.1% when the solvent was switched from PC to H 2 O and found that a H 2 O/PC ratio of 3/2 was the solution for the largest strain [50].…”
Section: Special Doping Counterions For Ppy Electroactuatorsmentioning
confidence: 99%